PENYULUHAN PERAWATAN AC SPLIT RUMAH TANGGA WARGA DI PARAKAN RT 009/RW09 PONDOK BENDA PAMULANG TANGERANG SELATAN - BANTEN - Miharja, Jaja; Giyanto, Giyanto; Thohirudin, Thohirudin; Santosa, Heru (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Community Service (PKM) is an integral part of the Tri Dharma of Higher Education which in its implementation is inseparable from the other two dharmas, and involves all academic community members: lecturers, students, education staff and alumni. Through PKM the academic community can be present in the midst of the community. Seeing the location of the campus which is not far from the location of Serpakan Parakan South Tangerang, it has become an obligation for Pamulang University (Unpam) to participate in helping various problems faced by the community both near and far. The use of air conditioning machines for the home is not an exclusive thing, but it is almost the general public to use a cooling machine for convenience. Therefore the engine cooling system maintenance becomes an important thing. PKM with the title: "Counseling Household Split Air Conditioning Care" To Warag Communities in Parakan RT 009 / RW09 Pondok Benda Pamulang Tangerang Selatan - Banten "in general went smoothly and in an orderly manner. The visitors were enthusiastic in listening to the explanations and demonstrations given. The enthusiasm of the visitors continued when the questions and answers surrounding the demonstration. This PKM activity was considered effective because the level of visitor interest was quite high in the engine maintenance system.